DARI DARUSSUFI MENJADI TARUNA RABBANI: SEBUAH STUDI TENTANG PERKEMBANGAN SEBUAH PESANTREN (2000-2020) - Sintia Yusda Putri; Abdul Salam (Jurnal Kronologi, 2022)
This study examines the history of an educational institution regarding the formation of a boarding school in Nagari Koto Sani and its development from Darussufi to Taruna Rabbani. This study uses the historical writing method with four stages, namely: heuristics, source criticism, interpretation and historiography. The result of this research is the formation of Islamic boarding schools in Nagari Koto Sani starting from da'wah activities which were pioneered by Pourku Syekh Muhammad Ali Hanafiah Ar Rabbani. Da'wah activities are carried out by spreading to several areas by carrying out recitation activities assisted by students and friends. Da'wah activities for areas outside the city of Padang were entrusted to Buya Hendra to develop to rural areas in Nagari Koto Sani. The formation of the Islamic boarding school in Nagari Koto Sani began in 2000. The construction of the Islamic boarding school was carried out in mutual cooperation with the main funding source from the recitation congregation. The Islamic boarding school since its inception has undergone four name changes from Darussufi, Tasawuf Rabbani, Rabbani and Taruna Rabbani which were founded on waqf land. The change in the name of the Islamic boarding school does not have a definite cause, but follows the times based on the demands of the needs which then develops formal educational institutions with elementary, junior high, high school levels. Keywords: Development, Islamic Boarding School, Darussufi, Sufism Rabbani, Rabbani, Taruna Rabbani